Local Cultural Heritage in the Experience of Residents of Rural Areas - Izabella Bukraba-Rylska; Maria Wieruszewska; Konrad Burdyka (Wieś i Rolnictwo)
Local Cultural Heritage in the Experience of Residents of Rural Areas [original title: Lokalne dziedzictwo kulturowe w doświadczeniu mieszkańców wsi], Institute of Rural and Agricultural Development, Polish Academy of Sciences, Scholar Publishing House, Warsaw 2017, ISBN 978-83-7383-876-5, p. 242.